Proximity: A Case Study of The Quest of Students’ Decision to Choose a Private University in Jakarta - Yosef Dema; Rita Eka Setianingsih; Yohanes L. Billy; Yanthy Herawaty Purnama (Jurnal Komunikasi dan Bisnis, 2023)
The process of selecting a university is complicated, impacted by a plethora of factors that shape students' decisions. The role of proximity, defined as the geographic distance between a student's place of residence and the location of the university, is important among these drivers. The purpose of this study is to give a case study that looks into the complex function of proximity in students' institution selection decisions. The study investigates how proximity influences several components of the university choosing process using a broad sample of students. The research combines surveys and interviews to provide both quantitative and qualitative insights into the interaction of factors influencing university choice, with a focus on proximity. The findings show that proximity has a significant impact on students' decisions, influencing convenience, housing expenses, family and community links, local employment options, sense of belonging, and overall cost concerns. This study contributes to a better understanding of the complex and dynamic elements that influence university selection and provides significant insights for universities and policymakers looking to better meet the requirements and expectations of prospective students.